Aromaterapi Sebagai Intervensi Non-Farmakologis Untuk Insomnia Pada Lansia: Studi di Rumah Sakit Mitra Medika Tanjung Mulia - Lia Effi Noviri; Yuniati Yuniati (Jurnal Kesehatan Amanah, 2024)
As individuals age, physiological changes and cognitive patterns can affect sleep quality, often leading to insomnia in older adults. This condition impacts quality of life and can be managed through pharmacological and non-pharmacological therapies. One proven non-pharmacological method is aromatherapy, which stimulates the nervous system to induce a relaxing effect. This study aims to evaluate the effectiveness of aromatherapy in reducing insomnia among older adults, using a quasi-experimental design with a pre- and post-test approach without a control group. The sample consisted of 30 elderly patients at Mitra Medika Tanjung Mulia Hospital. Data analysis revealed a significant difference (p = 0.001) before and after the intervention, confirming that aromatherapy effectively improves sleep quality in older adults. Therefore, this therapy can serve as an alternative method for managing insomnia in this age group.